2019
DOI: 10.1017/dsi.2019.77
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Guidelines in Design for Qualification Using Additive Manufacturing in Space Applications

Abstract: In recent years, reducing cost and lead time in product development and qualification has become decisive to stay competitive in the space industry. Introducing Additive Manufacturing (AM) could potentially be beneficial from this perspective, but high demands on product reliability and lack of knowledge about AM processes make implementation challenging. Traditional approaches to qualification are too expensive if AM is to be used for critical applications in the near future. One alternative approach is to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Furthermore, two other studies performed by the author contributed to the formulation of the framework. The first study focused on how qualification can be given increased attention during the development of AM components [22]. The findings showed that it would be beneficial to consider qualification as early as possible in order to design components that can be qualified, especially when designing for a new manufacturing process like AM.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, two other studies performed by the author contributed to the formulation of the framework. The first study focused on how qualification can be given increased attention during the development of AM components [22]. The findings showed that it would be beneficial to consider qualification as early as possible in order to design components that can be qualified, especially when designing for a new manufacturing process like AM.…”
Section: Methodsmentioning
confidence: 99%
“…The studies are hence referenced in the description of the framework where appropriate. The overall research process is shown in Figure 2 where the time frame for collection of the different data are indicated, as is the completion of the related papers [1,22,59]. Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations